The Strength of Proof of MKDKI Decisions in Medical Crime Cases in Indonesia - Muhammad Iffatul Lathoif; Budiarsih Budiarsih (Universitas PGRI Madiun, 2024)
The aim of this research is to determine the evidentiary strength of MKDKI decisions in Medical Crime Cases in Indonesia. MKDKI has the main objective of protecting patient safety, maintaining the quality of service to patients, and also maintaining the honor of the profession of doctors and dentists, which is actualized in the form of a trial in the medical sphere to find out whether a doctor or dentist has made a mistake in applying medical discipline knowledge or not. , institutionally, MKDKI is an autonomous institution from the Indonesian Medical Council whose duties are independent and responsible to the Indonesian Medical Council, then KKI in carrying out its duties is responsible to the president. Complaints submitted to MKDKI act to eliminate the right of every person to report any alleged medical crime to an authorized party or filing a lawsuit for damages in court. The type used in this research is normative legal research. This type of research places more emphasis on answering existing legal problems or issues, and this research uses several approaches, namely the statutory approach, the conceptual approach. (conceptual approach) and case approach (case approach). The results of this research show that the evidentiary strength of the MKDKI Decision which can be used as documentary evidence in medical criminal cases is as follows: 1) issued by an authorized official or issued by an official institution, 2) the MKDKI decision is produced through a legal and legitimate process , and 3) proof at a trial at MKDKI is the same as in a proceeding using criminal procedural law; and the examination process and trial process are carried out in depth, and carried out by parties who are competent in their fields